Chemical Characteristics of Cattle Manure and Its Suitability as Solid Organic Fertilizer in Tropical Agricultural Systems - Jaya, Galang Indra jaya; Mohammad Prasanto Bimantio; Amir Noviyanto; Raharjo, Dedy Tri; Keviana, Agesty (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Organic fertilizers play a crucial role in improving soil quality and supporting sustainable agriculture in tropical regions. This study evaluates the quality of cow manure based on the solid organic fertilizer standards set by the Indonesian Ministry of Agriculture. Laboratory analyses were conducted on key chemical parameters, including organic C, C/N ratio, moisture content, macronutrients (N, P₂O₅, K₂O), and pH, accompanied by weekly composting temperature observations. The results show that the manure had a high organic C content (34.91%) and an ideal C/N ratio (17.24), indicating mature and stable compost. Moisture content (17.84%) and pH (8.17) were within the acceptable standard range, confirming good storage stability and suitability for acidic tropical soils. Nitrogen content (2.03%) met the minimum requirement, while P₂O₅ (1.26%) and K₂O (0.23%) were at moderate levels typical of cattle manure. Temperature measurements during composting showed a normal decomposition pattern, increasing from 32°C in week 1 to about 33°C in weeks 2–3 before declining in week 4, supporting the maturity of the final product. Overall, the analyzed cow manure meets the quality standards for solid organic fertilizer and has strong potential as a soil amendment and supplementary nutrient source in tropical agricultural systems.